Approximation of the Localized Szász-Mirakjan-Durrmeyer Operators (Global Journal of Science Frontier Research, 2023)
In the present paper we localize the Sz sz-Mirakjan-Durrmeyer operators For which we discuss the convergence and the approximation and obtain theorems of convergence approximation and rate of approximation
Keywords: szász-mirakjan operators; szász-mirakjan-durrmeyer operators; localization; convergence; approximation